The Role of Adrenomedullin in the Renal NADPH Oxidase and (Pro)renin in Diabetic Mice - Michio Hayashi; Akihiro Tojo; Tatsuo Shimosawa; Toshiro Fujita (Journal of Diabetes Research)
Adrenomedullin has an antioxidative action and protects organs in various diseases. To clarify the role of adrenomedullin in diabetic nephropathy, we investigated the NADPH oxidase expression, renin-secreting granular cell (GC) hyperplasia, and glomerular matrix expansion in the streptozotocin (STZ)-induced diabetic adrenomedullin gene knockout (AMKO) mice compared with the STZ-diabetic wild mice at 10 weeks. The NADPH oxidase p47phox expression and lipid peroxidation products were enhanced in the glomeruli of the diabetic mice compared with that observed in the controls in both wild and AMKO mice. These changes were more obvious in the AMKO mice than in the wild mice. Glomerular mesangial matrix expansion was more severe in the diabetic AMKO mice than in the diabetic wild mice and exhibited a positive correlation with the degree of lipid peroxidation products in the glomeruli. Proteinuria was significantly higher in the diabetic AMKO mice than in the diabetic wild mice. The GC hyperplasia score and the renal prorenin expression were significantly increased in the diabetic AMKO mice than in the diabetic wild mice, and a positive correlation was observed with the NADPH oxidase expression in the macula densa. The endogenous adrenomedullin gene exhibits an antioxidant action via the inhibition of NADPH oxidase probably by suppressing the local renin-angiotensin system.